2015
DOI: 10.1016/j.nrl.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia de demencia de inicio precoz en Mar de Plata

Abstract: This study, conducted in a closed population, yielded an EOD incidence rate of 11 per 100 000 inhabitants/year. To the best of our knowledge, this is the first prospective epidemiological study in Argentina and in Latin America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
7
2
Order By: Relevance
“…For example, the Harvey and Ikejima studies identified a population prevalence of 54.0/100,000 and 51.7/100,000, respectively, for the 30-65 year age group but by contrast, a catchment area study conducted in Sydney produced a prevalence rate of 68.2/100,000 (95% confidence interval (CI): 54.9-83.4) (Withall, Draper, Seeher, & Brodaty, 2014). An Argentinian study using data from a 'closed-hospital population' with data extrapolated to the general population using national census data demonstrated an incidence rate of 11/100,000 (Sanchez-Abraham et al, 2015). The only UK study examining the incidence for all cases of primary dementia for the age range 45-64 years estimated it to be 11.5 cases per 100,000 person-years (95% CI 8.6-15.0, (Mercy, Hodges, Dawson, Barker, & Brayne, 2008)).…”
Section: Problems With Epidemiological Datamentioning
confidence: 99%
“…For example, the Harvey and Ikejima studies identified a population prevalence of 54.0/100,000 and 51.7/100,000, respectively, for the 30-65 year age group but by contrast, a catchment area study conducted in Sydney produced a prevalence rate of 68.2/100,000 (95% confidence interval (CI): 54.9-83.4) (Withall, Draper, Seeher, & Brodaty, 2014). An Argentinian study using data from a 'closed-hospital population' with data extrapolated to the general population using national census data demonstrated an incidence rate of 11/100,000 (Sanchez-Abraham et al, 2015). The only UK study examining the incidence for all cases of primary dementia for the age range 45-64 years estimated it to be 11.5 cases per 100,000 person-years (95% CI 8.6-15.0, (Mercy, Hodges, Dawson, Barker, & Brayne, 2008)).…”
Section: Problems With Epidemiological Datamentioning
confidence: 99%
“…There are confirmed rises of ALS from a number of Western clinical studies1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 25 as well as small increases in Asian and Latin American countries 18, 19…”
Section: Discussionmentioning
confidence: 91%
“…This was followed‐up in a second international study taking the results to 2010. The latter analysis used the later baseline years of 1989‐91, which confirmed the earlier onset of neurological morbidity and that neurological deaths continued to increase in the majority of the countries reviewed 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12. Rises in USA the over‐75s neurological deaths were considerable as the USA had significantly greater increases than fourteen of the other twenty nations, with threefold rises in American men and a fivefold increase in women in just 21 years 8.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations